Chains of Translation: On Being a Pacific Thoreauvian - Walls, Laura Dassow (Nordlit, 1998)
In memory of my brother. During the years I’ve been reading, writing, and thinking ‘professionally’ about Thoreau, I’ve kept a cedar frond tacked over my desk (…).